The Impact of Global Value Chain Embedding on Carbon Emissions Embodied in China’s Exports - Chen, Hanxue; Zhang, Caixia; Yin, Kedong (Frontiers in Environmental Science, 2022)
The impact of global value chain (GVC) division of labor on carbon emissions embodied in exports has attracted extensive attention from scholars, but existing studies have not distinguished the heterogeneous impact of different GVC embedding patterns on the carbon emissions embodied in exports. This study examines the effects of two GVC embedding patterns (forward embedding and backward embedding) on carbon emissions embodied in exports using data from 46 sectors in China from 2000 to 2014. The results show that both the backward and forward embedding patterns are characterized by increasing forward participation which increases carbon emissions embodied in Chinese exports. By contrast, the forward embedding pattern is characterized by increasing the length of the forward production chain and increasing the global value chain location index to help reduce the carbon emissions embodied in exports. There is significant heterogeneity in the effect of forward and backward embedding patterns on the carbon emissions embodied in exports. Increasing the length of forward production chains can effectively reduce the carbon emissions embodied in exports in labor-intensive and technology-intensive sectors but has no significant effect on capital-intensive sectors. Therefore, the Chinese government should start to reduce the carbon emissions embodied in China's exports by changing the GVC embedding pattern, improving the position of GVC embedding, and vigorously developing energy-saving and emission reduction technologies and clean industries, to help China achieve its CO2 reduction target in 2030.